Pertimbangan Hakim pada Perkara Dispensasi Nikah di Lingkungan Pengadilan Agama Tutuyan - Mujahid Assagaf (Al-Mujtahid: Journal of Islamic Family Law, 2023)
This study aims to determine the decision of the marriage dispensation at the Tutuyan Religious Court in completing the application for marriage dispensation and to find out the judge's considerations in deciding the case. The type of this research is field research (field research) with an empirical normative approach. The study results show that in considering the determination of the marriage dispensation, the Tutuyan Religious Court Judge is very concerned about the interests of the child for whom the marriage dispensation will be requested. As for the judge's considerations before deciding on a marriage dispensation case, the judge must listen to information from the applicant and the prospective partner for whom the dispensation is requested. After that, the judge will consider the data to determine whether the marriage can occur. As for Islam, the dispensation of marriage related to the age of marriage is based on the period of puberty for someone. It doesn't matter how old someone gets married. Scholars argue that this does not reduce the glory and purpose of the marriage contract. Keywords: Judge's Consideration; Marriage; Marriage Dispensation.  ABSTRAK Penelitian ini bertujuan untuk mengetahui putusan dispensasi nikah di Pengadilan Agama Tutuyan dalam menyelesaikan permohonan dispensasi nikah serta mengetahui pertimbangan hakim dalam memutuskan perkara tersebut. Adapun jenis penelitian ini adalah penelitian lapangan (field research) dengan pendekatan normatif empiris. Hasil penelitian menunjukkan bahwa dalam mempertimbangkan penetapan dispensasi nikah Hakim Pengadilan Agama Tutuyan sangat memperhatikan kepentingan dari anak yang akan dimintakan dispensasi nikah. Adapun pertimbangan hakim sebelum memutuskan perkara dispensasi nikah, yaitu hakim harus mendengarkan keterangan dari pemohon dan calon pasangan yang dimintakan dispensasi. Setelah itu, hakim akan mempertimbangkan keterangan tersebut untuk menentukan apakah pernikahan dapat dilangsungkan. Adapun dalam Islam, dispensasi nikah yang berkaitan dengan umur pernikahan berdasarkan masa baligh seseorang, bukan masalah usia seseorang akan menikah. Ulama berpendapat bahwa hal ini tidak mengurangi kemuliaan dan tujuan akad nikah.